Producing high‐quality precursor polymer and fibers to achieve theoretical strength in carbon fibers: A review. Issue 38 (10th June 2016) - Kaur, Jasjeet; Millington, Keith; Smith, Shaun
ABSTRACT: The precursor fiber quality has a large impact on carbon fiber processing in terms of its performance, production yield, and cost. Polyacrylonitrile precursor fibers have been used commercially to produce strong carbon fibers with average tensile strength of 6.6 GPa. There is a scope to improve the average tensile strength of carbon fibers, since only 10% of their theoretical strength has been achieved thus far. Most attempts to increase the tensile strength of carbon fibers have been made during the conversion of precursor fiber to carbon fiber. This review highlights the potential opportunities to enhance the quality of the polyacrylonitrile‐based precursor fiber during polymer synthesis, spinning, and postspinning. These high‐quality precursor fibers can lead to new generation carbon fibers with improved tensile strength for high‐performance applications. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43963. Abstract :